Migration of Population in Kashkadarya Region (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article analyzes the situation of migratory animals in the Kashkadarya oasis, the balance of internal and external migration, the change in the demographic composition of the population as a result of migration. In particular, the study of the growth of the urban population in relation to the rural population is mainly due to internal migration.